A Novel Experimental Model of Colorectal Endometriosis. (4th July 2018) - Prodromidou, Anastasia; Pergialiotis, Vasilios; Pavlakis, Kitty; Korou, Laskarina Maria; Frountzas, Maximos; Dimitroulis, Dimitrios; Vaos, Georgios; Perrea, Despina N.
ABSTRACT: Purpose: Endometriosis is a disease that affects 6–10% of the female population, mainly women of reproductive age, and causes a variety of cyclic symptoms. Deep infiltrating endometriosis and in particular bowel involvement presents a challenge for modern surgery. To date, there are no experimental animal models in this field, demonstrating experimental induction of endometriosis directly attached to surface of the colon imitating human colorectal endometriosis; hence, the implementation of novel pharmaceutical and surgical strategies for the management of colorectal endometriosis is mainly limited to clinical studies. Aim of the study: To investigate whether induction of colorectal endometriotic lesions in is feasible in rats. Materials and Methods: Twenty, female, adult, non-pregnant Sprague Dawley rats sustained uterine horn resection, which was then placed around the rectum of the rat with the endometrial surface in direct contact with the bowel serosa and approximated in the serosal surface of the colon with two sutures. Results: Two weeks following, surgery rats were euthanized and the bowel was surgically explored. The presence of a cystic lump at the site of the surgical intervention was evaluated macroscopically and microscopically. Histopathology documented the presence of cystic endometriosis. The endometriotic focus was adherent to the bowel wall by large fibrous nodules with concomitant replacement of part of the outer longitudinal muscle layer. Conclusions: The findings of our study support that the proposed experimental model of colorectal endometriosis is feasible, easily reproducible and may be implemented in future research in this field.